Log-Periodic Antenna for Partial Discharge Detection Application - Muhammad Faizol, Ahmad Zulbirri; Farid Zubir; Mohd Hafizi Ahmad; Norhafezaidi Mat Saman; Osman Ayop (ELEKTRIKA- Journal of Electrical Engineering, 2025)
This paper presents a design for a log-periodic antenna tailored for the purpose of detecting partial discharges (PD) in high-voltage electrical equipment. Partial discharge events can result in insulation damage, leading to costly repairs and an elevated risk of electrical failures. While the challenge of distinguishing between PD signals and noise remains, the utilization of a log-periodic antenna is recommended due to its numerous inherent advantages, such as high gain and directional capabilities. An electromagnetic log-periodic antenna proves to be an optimal choice for PD detection and monitoring, offering a broad frequency coverage, heightened sensitivity, precise PD localization, and early-stage detection capabilities. Remarkably, the log-periodic antenna is proficient at efficiently transmitting approximately 90 percent of the received power, rendering it a highly effective diagnostic tool for safeguarding the integrity of high-voltage equipment.